Efisiensi Penggunaan Cahaya Matahari dan Partisi Karbohidrat Tanaman Sorgum pada Berbagai Tingkat Pemupukan Nitrogen - Aznur, Firmansyah; ,, Suwarto; Purnamawati, dan Heni (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Light use efficiency (LUE) determines biomass production based on interception energy during photosynthesis. The product of photosynthesis is allocated to the plants organs based on the partitioning of carbohydrates. The LUE and carbohydrate partitioning are two important parameters in crop modelling. The research was conducted at Cikabayan experimental station of IPB, Bogor from July to November 2015. The experiment was designed according to a randomize block design with five replications. The fertilizer treatments rate were 0%, 50%, 100%, 150%, and 200% of reference N fertilization of 120 kg ha-1. The value of light use efficiency and the partition coefficient of sorghum were not affected by N fertilization. The value of light use efficiency is 1.41 g MJ-1. The carbohydrates partitioning was developed based on plant growth stage. The partition from the planting to the emergence stage (0 ≤ s ≤ 0.25) was 0.81 x s/0.25 root, 0 stem, 0.19 x s/0.25 leaves, and 0 panicle. The partition from the emergence to the maximum vegetative stage (0.25 < s ≤ 0.5) was 0.81-(0.59 x s/0.5) root, 0.14 x s/0.5 stem, 0.19 + (0.45 x s/0.5) leaves, and 0 panicle. The partition from the maximum vegetative stage to the flowering stage (0.5 < s ≤ 0.75) was 0.22 - (0.09 x s/0.75) root, 0.14 + (0.39 x s/0.75) stem, 0.64 - (0.46 x s/0.75) leaves, and 0.16 x s/0.75 panicle. The partition from flowering to the harvest stage (0.75 < s ≤ 1) was 0.13 - (0.13 x s) root, 0.53 - (0.52 x s) stem, 0.18-(0.18 x s) leaves, and 0.16 + (0.84 x s) panicle.Keywords: crop modelling, light use efficiency, N fertilizer, partitioning carbohydrates